EUS-FNA versus ERCP for tissue diagnosis of suspect malignant biliary strictures: a prospective comparative study - Moura, Diogo Turiani Hourneaux; de Moura, Eduardo Guidamarães Hourneaux; Matuguma, Sergio Eiji; dos Santos, Marcos Eduardo; Moura, Eduardo Turiani Hourneaux; Baracat, Felipe Iankelevich; Artifon, Everson LA; Cheng, Spencer; Bernardo, Wanderley Marque; Chacon, Danielle; Tanigawa, Ryan; Jukemura, José (Endoscopy International Open, 2018)
Background and study aims Biliary strictures are frequently a challenging clinical scenario and the anatomopathological diagnosis is essential in the therapeutic management, whether for curative or palliative purposes. The acquisition of specimens is necessary since many benign diseases mimic biliopancreatic neoplasms. Endscopic retrograde cholangiopancreatography (ERCP) is the traditionally used method despite the low sensitivity of biliary brush cytology and forceps biopsy. On the other hand, several studies reported good accuracy rates using endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA). The aim of this prospective study was to compare, the accuracy of EUS-FNA and ERCP for tissue sampling of biliary strictures. Patients and methods After performing the sample size calculation, 50 consecutive patients with indeterminate biliary strictures were included to undergo ERCP and EUS on the same sedation.The gold-standard was surgery or 6 months’ follow-up. Evaluation of the diagnostic indices (sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio), concordance and adverse events among the methods were performed. Also, subtype analyses of the techniques, anatomical localization and size of the lesion were included. Results The final diagnoses reported in 50 patients were 47 malignant, 1 suspicious and 2 benign lesions. 31 lesions were extraductal and 19 intraductal, 35 were distal and 15 proximal strictures. In the intention-to-treat analysis, the sensitivity and accuracy of EUS-FNA were superior than ERCP tissue sampling (93,8 %, 94 % vs. 60,4 %, 62 %, respectively) (P = 0.034), with similar adverse events. There was no concordance between the methods and combining both methods improved the sensitivity and accuracy for 97.9 % and 98 %, respectively. In the subtype analyses, the EUS-FNA was superior, with a higher accuracy than ERCP tissue sampling in evaluating extraductal lesions (100 % vs. 54.8 %, P = 0.019) and in those larger than 1.5 cm (95.8 % vs. 61.9 %, P = 0.031), but were similar in evaluating intraductal lesions and lesions smaller than 1.5 cm. There was no significant difference between the methods in the analyzes of proximal, distal and pancreatic lesions. Conclusion EUS-FNA is better than ERCP with brush cytology and intraductal forceps biopsy in diagnosing malignant biliary strictures, mainly in the assessment of extraductal lesions and in those larger than 1.5 cm. Combining ERCP with tissue sampling and EUS-FNA is feasible, the techniques have similar complication rates, and the combination greatly improves diagnostic accuracy.